High accuracy tracking reveals how small conservation areas can protect marine megafauna - Hays, Graeme C.; Mortimer, Jeanne A.; Rattray, Alex; Shimada, Takahiro; Esteban, Nicole (Ecological applications, 2021)
Space use estimates can inform conservation management but relaying high-accuracy locations is often not straightforward. We used Fastloc-GPS Argos satellite tags with the innovation of additional data relay via a ground station (termed a “Mote”) to record high volumes (typically >20 locations per individual per day) of high accuracy tracking data. Tags were attached in the Chagos Archipelago (Indian Ocean) in 2018–2019 to 23 immature turtles of two species for which there have been long-standing conservation concerns: 21 hawksbill turtles (Eretmochelys imbricata) and two green turtles (Chelonia mydas). Over long tracking durations (mean 227.6 d per individual), most turtles moved very little. For example, 17 of 21 hawksbill turtles remained continuously in the lagoon where they were equipped, with 95% and 50% utilization distributions (UDs) averaging only 1.03 and 0.18 km², respectively. Many individuals, and both species, could use the same small spaces, i.e., individuals did not maintain unique home ranges. However, three hawksbill turtles travelled hundreds of kilometers from the tagging site. Our results show that, for some large marine vertebrates, even small protected areas of only a few square kilometers can encompass the movements of a large proportion of individuals over long periods. High accuracy tracking may likewise reveal the details of space use for many other animals that move little and/or use important focal areas and where previous low-accuracy tracking techniques have tended to overestimate space use.